A Lean Implementation Success Model for the Construction Industry. Issue 3 (2nd July 2020) - Demirkesen, Sevilay; Bayhan, Hasan Gokberk
Abstract: The philosophy of Lean aims to maximize customer satisfaction while minimizing waste. However, complex, dynamic, and project-based nature of construction projects bring up uncertainties in achieving benefits of Lean implementations (i.e., improvements in the schedule, budget, safety, and quality). The major objective of this study is to propose a comprehensive success model for Lean implementation in the construction industry. Within this context, a set of success criteria are identified based on extensive literature research, and the criteria set are classified into seven categories namely the financial, managerial, technical, workforce, culture, government, and communication. Then, an analytical network process (ANP) model is developed in order to reveal the links between the attributes of success while computing the importance weights of these attributes by the expert team of five. Data used for the ANP model are collected from eight experienced civil engineers through a questionnaire administered in two parts. Delphi method was adopted in the questionnaire administration, where several rounds of questionnaires were sent to the group of experts. Lean training, availability of Lean tools and techniques and market share were found as the most important success factors of Lean implementation. The performance of the proposed model is tested on six different construction projects and the results were evaluated to validate the ANP model. The study is expected to lead Lean practitioners and Engineering Managers with overcoming challenges in Lean implementation process and guide them about success parameters to consider and prioritize tasks when implementing Lean in their organizations.